Description of Rhodnius montenegrensis n. sp. (Hemiptera: Reduviidae: Triatominae) from the state of Rondônia, Brazil - Da Rosa, João Aristeu; Rocha, Cláudia Solano; Gardim, Sueli; Pinto, Mara Cristina; Mendonça, Vagner José; Filho, Júlio César Rente Ferreira; de Carvalho, Elaine Oliveira Costa; Camargo, Luís Marcelo Aranha; de Oliveira, Jader; Nascimento, Juliana Damieli; Cilense, Mario; Almeida, Carlos Eduardo (Zootaxa, 2012)
We present here a multisource approach that takes advantage of several disciplines to address a taxonomic issue. A triatomine related to Rhodnius robustus Larrousse, 1927 was recently found in the state of Rondônia, Brazil. The name Rhodnius montenegrensis n. sp. is suggested because it was found in the municipality of Monte Negro. The main differences between these two species can be detected in the female and male genitalia, but there are also noticeable differences in their eggs. Molecular analysis using PCR-RFLP technique and Bayesian inferences based on a fragment of the Cytochrome b (Cyt b) gene corroborated the morphological findings. We used this integrative approach to address the taxonomic decision for a new Rhodnius species and its relationship with others of this genus. Results obtained herein stress that morphology must be used as the major approach for obtaining phenotypic information, and molecular data should be taken as a complementary tool.